Penggunaan Kombinasi Auksin dan Sitokinin untuk Menginduksi Tunas pada Kultur Jaringan Sengon (Falcataria moluccana)menggunakan bagian Kotiledon - Toni Herawan; Burhan Ismail (Jurnal Pemuliaan Tanaman Hutan, 2009)
The purpose of this research is to examine the effect of auxin (NAA) and cytokinin (BAP) on shoot initiation in tissue culture of sengon (Falcataria moluccana)using cotyledon segment. Cotyledon segments were colleect from aseptic seedlings. Cotyledon segments were aseptically cultured on a murashige and  Shoog’s (MS) medium containing different concentrations of Benzyl-amino-purine (BAP) ranging from 1 to 3 mg/l and Naphtalene-acetic-acid (NAA) ranging from0,01 to 0,03 mg/l. Result of analysis of variance inicates that plant groeth regulator of BAP and NAA had significant effect on shoot formation up to 4 months age. The subsequent Duncan Multiple Range Test indicates that concentration of 0,001, 0,02 and 0,03 mg/l gave no significant effect on shoot formation and shoot growth